Beyond the street: the institutional life of rap - Bramwell, R; Butterworth, J (Cambridge University Press, 2020)
This article draws on ethnographic fieldwork conducted over the course of one year in London and Bristol to examine the performance of rap in English youth centres. Youth centres play a significant role in supporting and shaping rap culture. However, historically dominant narratives within hip-hop studies and hip-hop culture depict rap as a vernacular cultural form that emerges from ‘the street’, and which derives its authenticity through its relation to ‘the street’. We seek to move beyond such discourses and towards a recognition of the institutional processes, structures and networks that shape and sustain rap culture. Our focus on the institutional life of rap leads to an analysis of the various possibilities, limitations, and tensions that arise in the coming together of public funding, and social policy priorities, local organisations, and black vernacular culture.